Restrictions on Some Western Songs: A Counter Hegemony Effort by the West Java Regional Indonesian Broadcasting Commission - Andre Ikhsano; Yolanda Stellarosa (Ikatan Sarjana Komunikasi Indonesia, 2020)
Restriction on the broadcasting of 17 western songs considered full of sexual aspects in the Indonesian province of West Java has given rise to polemic and criticism. Various reactions, both negative and positive, emerged. Instead of supporting the restriction the Indonesian public appeared to blatantly oppose the policy made by the West Java Regional Indonesian Broadcasting Commission (KPID). It is interesting to analyze and study this phenomenon more deeply through the great concepts of Gramsci’s counter hegemony. Of course, a mature and strategic counter hegemony is needed to counter western music hegemony in the country. The study of counter hegemony has not been widely discussed, especially when it comes to the counter of the counter hegemony itself and this can be the novelty of this study. This phenomenon is analyzed through critical perspective by conducting literature study in several online media sites related to the topic of this research. The results show that the counter hegemony which was not carried out systematically and strategically with regard to the restrictions on the broadcasting of 17 western songs in the province of West Java did not yield a fruit in the form of the hegemony’s downfall. The hegemony of western songs remains strong. The failure of counter hegemony will strengthen the hegemony of western songs in Indonesia. For its part, it is necessary to have mature planning and strong collaboration between political society and civil society to make the counter hegemony run well in an attempt to undermine the hegemony.